2000
DOI: 10.1007/bf02704315
|View full text |Cite
|
Sign up to set email alerts
|

Novel application of Wiener vis-à-vis Szeged indices: Antitubercular activities of quinolones

Abstract: The paper gives a brief account of the recently introduced Szeged index (Sz). Using this index antitubercular activities of N-2,4-difluorophenyl quinolones are subjected to quantitative structure-activity relationship analysis. The potential of Sz related to the Wiener index (W) is critically discussed. In addition, Huckel molecular orbital energies: E HOMO , E LUMO and E total were also used for comparing and modelling antitubercular activities of the quinolones. The results, based on univariate as well as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…At first, Wiener index was used for predicting the boiling points of paraffins [105], but later strong correlation between Wiener index and the chemical properties of a compound was found. Nowadays this index is a tool used for preliminary screening of drug molecules [1]. Wiener index also predicts binding energy of protein-ligand complex at a preliminary stage.…”
Section: Introductionmentioning
confidence: 99%
“…At first, Wiener index was used for predicting the boiling points of paraffins [105], but later strong correlation between Wiener index and the chemical properties of a compound was found. Nowadays this index is a tool used for preliminary screening of drug molecules [1]. Wiener index also predicts binding energy of protein-ligand complex at a preliminary stage.…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between Sz index and logP of n-alkanes [73] was reported as below: The relationship between Szeged index of a rooted-graph (Sz(s)), which is also used as a substitutent constant, and anti-tuberculotic activity of some N -2,4-difluorophenol quinolones was also developed [49,50,56].…”
Section: Relationship Between Sz Index and Logp Of Nalkanes [73]mentioning
confidence: 99%
“…The basicity (pK 1 ) of sulfonamide Schiff's bases [113] could be accounted for by using Szeged index in multiparametric regression analysis: pK 1 = 1.1802 Sz -0.0138 P zz + 13.625 (56) Our research pertaining to the use of Szeged index (Sz) in developing QSAR models for bio-medicinal activity of organic compounds acting as drugs has indicated that in many cases models with better statistics are obtained in multi-parametric models in that Sz index has to be combined with some additional molecular descriptors including other topological indices and indicator parameters. We also observed that, in some cases, it was necessary to split the data into two or more categories depending upon the nature and type of compounds involved in the heterogeneous set.…”
Section: Basicity (Pk 1 ) Of Sulfonamide Schiff's Bases [113]mentioning
confidence: 99%
“…The biological activity can be optimized by choosing such substituents which would enhance desired physico-chemical properties. Agrawal et al [19][20][21][22][23][24][25][26][27][28] have reported QSAR studies on different organic drug compounds.…”
Section: Introductionmentioning
confidence: 99%